2008
DOI: 10.1016/j.brainres.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy induces functional asymmetry on an odor memory/discrimination test

Abstract: The secondary afferents of the olfactory system largely project to the ipsilateral cortex without synapsing in the thalamus, making unilateral olfactory testing a useful probe of ipsilateral hemispheric activity. In light of evidence that lateralized performance on some perceptual tasks may be influenced by estrogen, we assessed left:right nostril differences in two measures of olfactory function in 14 post-menopausal women receiving estrogen replacement therapy (ERT) and 48 postmenopausal women receiving no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(43 reference statements)
2
14
0
Order By: Relevance
“…None of the participants in the current study displayed total anosmia which was the exclusion criteria for the current study and therefore, all participants presented olfactory performances in OIT to a standard held in line with the existing olfactory research (Doty et al, 1984, 1995). All participants scored between 8 and 12 out of 12 in the ODMT which corresponds to healthy ranges, in line with existing literature (Doty et al, 1984, 1995; Choudhury et al, 2003; Doty, 2003). In this context, all participants were qualified to take part in the current study.…”
Section: Resultssupporting
confidence: 89%
“…None of the participants in the current study displayed total anosmia which was the exclusion criteria for the current study and therefore, all participants presented olfactory performances in OIT to a standard held in line with the existing olfactory research (Doty et al, 1984, 1995). All participants scored between 8 and 12 out of 12 in the ODMT which corresponds to healthy ranges, in line with existing literature (Doty et al, 1984, 1995; Choudhury et al, 2003; Doty, 2003). In this context, all participants were qualified to take part in the current study.…”
Section: Resultssupporting
confidence: 89%
“…However, the observed tendency for HIV-infected men to develop olfactory identification dysfunction more than the HIV-infected women may be related to a difference in their reproductive hormones. 50 A significant correlation existed between latest CD4 cell count and OT only. Brody et al 51 reported no correlation between olfactory function and CD4 count.…”
Section: Discussionmentioning
confidence: 91%
“…However, the observed tendency for HIV-infected men to develop olfactory identification dysfunction more than the HIV-infected women may be related to a difference in their reproductive hormones. 50…”
Section: Discussionmentioning
confidence: 99%
“…Female rodents show when they are most fertile and exhibit the greatest discrimination between sexual potent and impotent males [ 63 ]. In humans, female changes in olfactory preference to male odors correlate with phases of fertility during their menstrual cycle [ 11 , 46 , 45 , 64 ]. The enhancement and attenuation of olfactory sensitivity according to the circulating concentrations of steroid hormones may trigger appropriate behavioral and neuronal mechanisms in reproductively active and inactive individuals.…”
Section: Discussionmentioning
confidence: 99%